2013
DOI: 10.1017/s0043933913000810
|View full text |Cite
|
Sign up to set email alerts
|

Electrolytes, dietary electrolyte balance and salts in broilers: an updated review on growth performance, water intake and litter quality

Abstract: Electrolytes (sodium, potassium and chloride) are compounds that dissolve into positive and negative particles in solution. The relationship between these compounds, known as the 'dietary electrolyte balance' (DEB), is affected by either electrolyte or its supplemental salt source. The National Research Council recommended 0.20% sodium, chloride, and 0.30% potassium for starter phase and lower doses of sodium and chloride for the finisher phase of broilers. However, these requirements are increased under heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 58 publications
1
19
0
2
Order By: Relevance
“…Several studies have shown that dietary electrolyte (Na, K and Cl) balance is an important factor influencing excreta moisture and FPD severity in poultry. In particular, as has been found in many studies with broiler chickens and turkeys, high dietary levels of Na and K as well as high dietary electrolyte balance increase water intake and litter moisture (Borges et al., ; Ravindran et al., ; Koreleski et al., , ; Mushtaq et al., ; Jankowski and Zdunczyk, ), which in turn is a factor leading to increased FPD severity. The result of the study by Cengiz et al.…”
Section: Diet Compositionmentioning
confidence: 84%
“…Several studies have shown that dietary electrolyte (Na, K and Cl) balance is an important factor influencing excreta moisture and FPD severity in poultry. In particular, as has been found in many studies with broiler chickens and turkeys, high dietary levels of Na and K as well as high dietary electrolyte balance increase water intake and litter moisture (Borges et al., ; Ravindran et al., ; Koreleski et al., , ; Mushtaq et al., ; Jankowski and Zdunczyk, ), which in turn is a factor leading to increased FPD severity. The result of the study by Cengiz et al.…”
Section: Diet Compositionmentioning
confidence: 84%
“…Some studies have shown that the increases in Na + and Cl − are linear with water consumption and the moisture content of excreta in broilers (Jankowski, Zduńczyk, Juśkiewicz, & Kwieciński, ; Mushtaq, Pasha, Mushtaq, & Parvin, ). This is inconsistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Tijdens periodes van potentiële hittestress wordt het drinkwater vaak aangevuld met elektrolyten (Ahmad and Sarwar, 2006;Lin et al, 2006;Mushtaq et al, 2013;Oliveira et al, 2016). Elektrolyten zijn mineralen in het bloed en van belang voor de normale celfunctie en -groei.…”
Section: Elektrolytenunclassified
“…Echter experimenten naar de beïnvloeding van de elektrolytenbalans geven onduidelijke resultaten en ondersteunen het voorgaande niet (Ahmad and Sarwar, 2006;Borges et al, 2004;Koike et al, 1983;Mushtaq et al, 2014;Mushtaq et al, 2013;Oliveira et al, 2016;Schafer, 2012). Jong et al, 2015;Pesti et al, 1985;Pesti and Marks, 1983;Shepherd and Fairchild, 2010).…”
Section: Elektrolytenunclassified